The Role of Indonesian Human Resources in Developing MSMEs Facing the Industrial Revolution 4.0 - Rosmadi, Maskarto Lucky Nara; Herlina, Herlina; K, Endah Widiastuti; Tachyan, Zaenudin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to determine the role of Indonesian HR in increasing MSMEs facing the 4.0 industrial revolution. The research method used is a qualitative method with an analytical and explorative descriptive approach. From the results of the research conducted, it was found that the quality of human resources in the Dzul Collection bag industry was less supportive for developing the industry due to the low level of education and lack of innovation to produce quality products. To improve the quality of human resources, effective and efficient steps are needed through sharing knowledge and exchanging knowledge among fellow employees and training. Through these activities, it is expected that the development of this industrial business can be realized, especially in the face of free markets and global economic competition.